Two-step inexact Newton-like method for solving generalized inverse eigenvalue problems - Liuqing Hua; Wei Ma (Results in Applied Mathematics)
In this paper, based on two-step Newton iterative procedure, we propose a two-step inexact Newton-like method for generalized inverse eigenvalue problems. Under some mild assumptions, our results show that the two-step inexact Newton-like method is super quadratically convergent. Numerical implementations demonstrate the effectiveness of the new method.